A Rapid Total Synthesis of Ciprofloxacin Hydrochloride in Continuous Flow. Issue 30 (20th June 2017) - Lin, Hongkun; Dai, Chunhui; Jamison, Timothy F.; Jensen, Klavs F.
Abstract: Within a total residence time of 9 min, the sodium salt of ciprofloxacin was prepared from simple building blocks via a linear sequence of six chemical reactions in five flow reactors. Sequential offline acidifications and filtrations afforded ciprofloxacin and ciprofloxacin hydrochloride. The overall yield of the eight‐step sequence was 60 %. No separation of intermediates was required throughout the synthesis when a single acylation reaction was applied to remove the main byproduct, dimethylamine. Abstract : Rapid assembly of five building blocks to make the antibiotic ciprofloxacin was achieved in nine minutes in flow. A total of six reactions took place in five reactors to afford ciprofloxacin sodium salt. Simple offline pH adjustment, filtration and crystallization afforded ciprofloxacin hydrochloride crystal.